1990
DOI: 10.1093/jnci/82.17.1407
|View full text |Cite
|
Sign up to set email alerts
|

Maize and Risk of Cancers of the Oral Cavity, Pharynx, and Esophagus in Northeastern Italy

Abstract: The relationship between maize consumption and risk of cancer of the upper digestive tract was investigated in 107 patients with oral cancer, 107 with pharyngeal cancer, 68 with esophageal cancer, and 505 hospital controls who permanently resided in Pordenone Province in the northeastern part of Italy. The analysis was restricted to males. The population of this province has a high incidence of these neoplasms and shows particularly elevated levels of alcohol and tobacco use, in addition to high maize consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
380
5
18

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(420 citation statements)
references
References 0 publications
17
380
5
18
Order By: Relevance
“…21,22 Thus, the finding that whole grain and other plant foods are inversely related to the incidence of upper aerodigestive cancer suggests many possible avenues for research into cancer mechanisms. As in other studies, [23][24][25][26][27] we found that cigarette smoking was strongly positively associated with upper aerodigestive tract cancers. In our study, alcohol use was positively associated with upper aerodigestive cancers but lost statistical significance after adjustment for age, smoking and dietary factors.…”
Section: Discussionsupporting
confidence: 88%
“…21,22 Thus, the finding that whole grain and other plant foods are inversely related to the incidence of upper aerodigestive cancer suggests many possible avenues for research into cancer mechanisms. As in other studies, [23][24][25][26][27] we found that cigarette smoking was strongly positively associated with upper aerodigestive tract cancers. In our study, alcohol use was positively associated with upper aerodigestive cancers but lost statistical significance after adjustment for age, smoking and dietary factors.…”
Section: Discussionsupporting
confidence: 88%
“…These neoplasms are strongly related to smoking and alcohol consumption (Franceschi et al, 1990;Negri et al, 1993), but several studies have related various aspects of diet to the risk of oral/pharyngeal and oesophageal cancers (Trichopoulou et al, 2000;Zheng et al, 1992). A diet rich in animal fats has been associated with an increased risk of these cancers (Launoy et al, 1998), but the epidemiological evidence on the role of meat consumption is not consistent (Franceschi et al, 1999b).…”
mentioning
confidence: 99%
“…The multivariate odds ratio was 2.46 for heavy drinkers non-smokers, and 9.38 for current smokers non-drinkers. Alcohol drinking and tobacco smoking increase the risk of laryngeal cancer, and show a multiplicative effect on risk (IARC, 1986(IARC, , 1988Tuyns et al, 1988;Franceschi et al, 1990;Sankaranarayanan et al, 1990;Dosemeci et al, 1997). In developed countries, laryngeal cancer is extremely rare in individuals who do not smoke and do not drink alcohol and information on risk in such people is therefore limited.…”
mentioning
confidence: 99%